Tug of war: street trading and city governance in Kumasi, Ghana. Issue 7 (2nd October 2016) - Owusu-Sekyere, Ebenezer; Amoah, Samuel Twumasi; Teng-Zeng, Frank
ABSTRACT: Kumasi, Ghana, has witnessed accelerated population growth in the past two decades, leading to a significant increase in joblessness following years of economic decline and labour market liberalisation. As a survival strategy, residents have resorted to street trading, making it an important source of livelihood. However, its associated implications for urban governance and management has placed city authorities in the spotlight over the years. Examining the daily struggles that occur between city managers and street traders, this article finds that various strategies adopted by city authorities to decongest the streets have proved futile. Rethinking what could be a sustainable strategy for decongesting the streets of traders, the article concludes that chasing the traders out of the streets is not the panacea to solving the problem unless well coordinated land-use planning and appropriate regulations are competently enforced.